Planejamento e desenvolvimento de novos agentes anti - Mycobacterium fortuitum - Jortieke, Carlos Roberto Tavolari (2025)
Mycobacterium fortuitum is a rapidly growing nontuberculous mycobacterium (NTM), an opportunistic pathogen commonly found in natural environments, particularly in soil and contaminated water sources. This species causes both pulmonary and extrapulmonary infections, being especially characterized by cutaneous infections. In recent years, its prevalence has increased, as well as its antibacterial resistance to known antibiotics. Consequently, there is a growing need for the development of new treatment options for infections caused by this microorganism. Thus, this work aimed to design and develop new agents with anti-Mycobacterium fortuitum activity. The study was conducted in two main stages. The first was a literature review focusing on the main active Hit compounds against this Mycobacterium, divided into synthetic, semi-synthetic, and natural compounds. This stage resulted in an article entitled “Advances in antibacterial agents for Mycobacterium fortuitum”, presented in Chapter 1. The second stage involved the synthesis of derivatives containing a furopyridine ring, focusing on three key positions of this heterocyclic core, inspired by other compounds reported with some antimycobacterial activity. The synthetic phase was divided into three series of compounds: derivatives with variations at C-2 (using oleic and palmitic fatty acids, through a heterocyclization reaction, yielding 2 compounds); derivatives with variations at C-3 (using cyclopropylamine and cycloheptylamine, through amide coupling, yielding 2 compounds); and derivatives with variations at C-6 (using pyrrolidine, homopiperidine, azetidine, and cycloheptylamine, through a Buchwald-Hartwig amination or through a nucleophilic attack on a carboxyl group, yielding 5 compounds). After structure characterization of these 10 new compounds, the Minimum Inhibitory Concentration (MIC) was obtianed against Mycobacterium fortuitum. This allowed us to establish Structure-Activity Relationship, in which the volume at position 6 appears to be highly restricted to the fivemembered ring (pyrrolidine) directly attached to the pyridine moiety (MIC = 2.6 µM). This compound had already been reported to exhibit activity against Mycobacterium tuberculosis, demonstrating the potential repurposing of this Hit compound for the treatment of multiple types of infections caused by Mycobacteria.